Application of biopesticides and fungicides for the control of fruit rot of custard-apple - N. C. CHATTERJEE2*, M. R. CHAKRABORTY1, S. OJHA2 and (Indian Phytopathology, 2012)
Annona squamosa Linn. (Custard-apple) belonging to the family Annonaceae is one of the best tropical fruits of our country. Fruit rot of custard-apple caused by Phoma sp is a major constraint in production that causes substantial loss in yield. Fruit rot was characterized by blackening of the entire fruit which gradually became stony with progressive advancement of the disease thereby posing a sight of hanging coal-tar balls ornamented in the greens of the plant. Effort was made to find out the biospectrum of fungicides and biocides against the pathogen with an object to formulate an application schedule for controlling the disease. Among the fungicides viz., Bavistin, Captan, Tridemorph, Topsin, Mancozeb, Vitavax, Hi-dice trialed at different concentrations; bavistin (88%) followed by hi-dice (81%) significantly controlled the vegetative growth of the pathogen and found most effective at minimum concentration. Biocidal effect of ten plants species viz., Allium sativum, Allium cepa, Azadirachta indica, Eucalyptus globutus, Zingiber officinal, Ocimum sanctum, Cymbopogon citratus, Lantana camara, Adhatoda vasica and Vitex negundo on growth of the pathogen was studied. Among them, neem (A. indica) extract was the best showing 76% inhibition of the fungal growth followed by C. citratus (70.9 %). In the field trial among the fungicides, bavistin (0.1%) along with A. indica formulation were sprayed twice at 7 days interval immediately after appearance of the symptoms and the disease severity was found to be significantly reduced.